Definição da Identidade Sonora de um Programa de Rádio - Antena 3 - Bruno Miguel Frade Monteiro (2018)
In this dissertation, we propose ourselves to define and produce the sonic identity of a radio program, which name is "Indiegente" which is broadcasted in the portuguese radio station called "Antena 3". Due to the lack of documentation focused in projects of this nature, in an academic and professional level, will be necessary to resort to relative areas, and not less important ones, like Psychology, Phisiology, Marketing and Comunication. Only like this will be possible to define an effective reasoned method, to the criation of a sonic identity. In addition to the criation of a relevant documental contribution to future works and studies in several areas, this dissertation will be focused on the practical implementation of our project, where we will renew a full sonic identity, and contribute to a dinamization of the radio station we're working on, that will be benefic for it in terms of marketing and comunication. In this dissertation, beyond the contextualization and identification of the motivations of this investigation, we will do a review of all the literature relative to several areas that we consider relevant to similar projects, and also a case of study focused in the radio station we're working on. Based on a logical reasioning that relates all the bibliographic research with the content extracted from our case of study, we will define a set of methods and guidelines that will determine the criation of the sonic identity of the program "Indiegente". After the practical implementation of this project, will be made a concrete avaliation, by relevant entities, that will justify the validation of this project.